Diseño de un plan de desarrollo turístico para el sector de Loreto Pedregal, de la parroquia Machachi, cantón Mejía, provincia Pichincha - Masapanta Inga, Christian Dario (2016)
In Pichincha province, Mejia canton, Machachi Parish we found Loreto Pedregal, established as one of the main tourist attractions because its location is in the middle of the Andean highlands of Ecuador, crossed by the Route of the Volcanoes and especially the Cotopaxi Volcano. Its importance highlight the environmental and cultural part but nevertheless the tourism development in the area has been hampered by the lack of attention of the community and municipal governments, resulting in poor roads, poor signage, poor promotion tourist, industry and seasonality throughout the year. Design a tourism plan will provide with the guides that drive on the sector to progress based on the principles of sustainability (environmental, cultural and economic). The realization of this project was divided into three parts, the first was the development of a descriptive diagnosis determine its main strengths, weaknesses, opportunities and threats. The second part was to realize an inventory of the AFA factors, which consist of the list of natural and cultural attractions, its facilities with the chips of inventory of MINTUR, and thirdly the development of programs and projects under the Logical Framework methodology. To achieve the tourism sector potentiation we created three programs like to tourist program itself consisting in four projects that help solve problems in signage, seasonality, promotion and tourist interpretation, environmental program has a proposed to use and management of natural resources aimed at the conservation and care of the moor and cultural program consisting of three projects which seeks to ensure the safety of residents and visitors both in the field and conducting tourism activities, the implementation of this plan has been estimated in five years.